A percepção de privacidade do internauta brasileiro à luz da tipologia de Sheehan: uma análise exploratória - Dunaevits, Ilan (2012)
Advances in information technology, especially in the virtual world, while creating new opportunities for businesses and more convenience to users, also generates conflicting interests between these two parties, emerging paradoxes in the relationship between them when it comes to personalization-privacy tradeoff. One of the consequences is the lack of consumer confidence in exposing their personal data in the online environment, which in turn, impacts the capacity of the e-commerce. One of the possible solutions pointed out by several scholars to manage the dilemma is to search for solutions that balance individual privacy and the needs for information disclosure. As part of this path, which looks for the meaning and value of privacy nowadays, are studies of typology, which, though numerically small — especially in the online environment — represent the efforts to arrive at a conceptualization of what is the nature of private. The typologies allow developing strategies and solutions in tune with the many social demands. The purpose of this study, therefore, is to replicate a particular model of privacy typology in Brazil. The choice fell on a study of Sheehan (2002), developed and tested in the U.S. environment. Translating the model to a group of 190 individuals in Brazil, we found that among the four studied variables (gender, age, education level and family income), only age was significant for privacy, with little more than 20% of variability. The level of education, which proved influential in American Internet users, did not show any relevance between the Brazilians. The differences in results can be attributed to several factors, with emphasis on the role played by cultural systems. Future studies should pursue such discrepancies to meet the challenge of privacy in the virtual field and benefit both individuals and the e-commerce.